Behavioral Economics and Neuroeconomics in Studied the Intuition - Andreev, Rumen (Research Papers, 2019)
The aim of the article is to present the importance and applicability of intuition in the modern world, as well as the study of behavioral economics. An interdisciplinary approach has been used, with a comparative and critical analysis of different concepts of behavioral economics, neuroeconomics and cognitive psychology. The intuition is presented by presenting the anatomy of left and right brain thinking, the rational and automatic thinking system, the influence of information technologies on its acquisition.
Keywords: Intuition; Heuristics; Behavioral economics; Neuroeconomics